Niches, interspecific associations, and community stability of main understory regeneration species after understory removal in temperate forests - Zhang, Yanyan; Zhou, Wangming; Yuan, Quan; Deng, Jiaojiao; Zhou, Li; Yu, Dapao (Frontiers in Plant Science, 2024)
Introduction Understory removal is frequently used to relieve the renewal pressure on trees and promote the growth capability of trees for maintaining community stability, while the lack of previous study on temperate forests limits our assessment of the effectiveness of this essential management measurement. Methods In this study, we calculated the niche characteristics and interspecific association of main understory species and community stability in temperate forests [original broad-leaved Korean pine forest (BKF), Betula platyphylla secondary forest (BF), and Larix gmelinii plantation (LF)] after understory removal for characterizing the resource utilization capacity of the regeneration trees. Results During the restoration stage, the niche breadth of understory plants with similar habits varied across stands and layers; regeneration tree species with heliophile and semishade occupied a larger niche in BKF and LF, while it was the opposite in LF. Niche overlap among heliophile regeneration trees increased in both BKF and BF, but not in LF. The interspecific association among main species revealed that the distribution of each species was independent and the interspecific association was loose and it varied in different forests and different light-demanding species with regeneration trees. The stability of shrub communities in BF and LF improved whereas that of BKF declined, while that of the herb communities of corresponding forests showed the opposite state. Discussion Our study demonstrated that the effectiveness of understory removal depends on species’ ecological habits, which enhances the renewal and resource utilization capacity of regeneration tree species in temperate forests and shrub community stability in BF and LF.